STRATEGI MODALITAS PEREMPUAN MUDA DALAM KONTESTASI POLITIK LOKAL (Studi Kasus Dinda Ari Ayu Isnani pada Pemilu Legislatif Kota Semarang 2024) - Nada Shabah; Fitriyah Fitriyah (Journal of Politic and Government Studies, 2026)
Modalities refer to the resources possessed and managed by political actors to gain and maintain power in a political contestation. In legislative elections, political, social, and economic modalities are crucial factors influencing a candidate’s success, including young women who often face structural barriers in the political arena. On the other hand, women’s representation in Indonesia is promoted through an affirmative action policy requiring a minimum quota of 30% women in legislative candidacy. However, fulfilling the quota administratively does not automatically guarantee 1Mahasiswa Ilmu Pemerintahan Universitas Dipenogoro 2Dosen Ilmu Pemerintahan Universitas Diponegoro electoral success. This study aims to analyze the modality strategies employed by Dinda Ari Ayu Isnani in winning a seat in the 2024 Semarang City Legislative Election. As a 24-year-old young woman and a newcomer to politics, Dinda successfully secured a seat in the Semarang City Regional House of Representatives (DPRD). This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews with the candidate, campaign team members, and voters, supported by document analysis. The data were analyzed using the framework of political, social, and economic modalities. The findings reveal that Dinda’s victory resulted from the integrated management of various modalities. Social modality played a role in building voter trust through family networks and the performance of the campaign team. Political modality was reflected in party support and easier access to the candidacy process, while economic modality functioned as operational support for campaign activities. The findings also indicate that affirmative action policies are more effectively utilized by candidates who already possess sufficient modalities. Therefore, the ownership and management of modalities are key factors in determining the electability of young women in local political contestation.